Aedes aegypti and Aedes albopictus (Diptera: Culicidae): coexistence and susceptibility to temephos, in municipalities with occurrence of dengue and differentiated characteristics of urbanization Aedes aegypti e Aedes albopictus (Diptera: Culicidae): coexistência e susceptibilidade ao temephos, em municípios com ocorrência de casos de dengue e diferentes características de urbanização - Josiane Somariva Prophiro; Onilda Santos Silva; Jonny Edward Duque Luna; Carla Fernanda Piccoli; Luiz Alberto Kanis; Mario Antonio Navarro da Silva (Sociedade Brasileira de Medicina Tropical (SBMT), 2011)
INTRODUCTION: The aim of the present study was to verify the coexistence between Aedes aegypti and Aedes albopictus populations in municipalities of the States of Paraná and Santa Catarina with different urbanization profiles where dengue occurs and evaluate their susceptibility to the organophosphate temephos. METHODS: The number of eggs per ovitrap were counted and incubated for hatching to identify the species. Data analysis of the populations was conducted to determine randomness and aggregation, using the variance-to-mean ratio (index of dispersion). Susceptibility to temephos was evaluated by estimation of the resistance ratios RR50 and RR95. Aedes aegypti samples were compared with the population Rockefeller and Aedes albopictus samples were compared with a population from the State of Santa Catarina and with the Rockefeller population. RESULTS: Coexistence between Aedes aegypti and Aedes albopictus and the aggregation of their eggs were observed at all the sites analyzed in the State of Paraná. CONCLUSIONS: All the Aedes aegypti populations from the State of Parana showed alteration in susceptibility status to the organophosphate temephos, revealing incipient resistance. Similarly, all the Aedes albopictus populations (States of Paraná and Santa Catarina) presented survival when exposed to the organophosphate temephos. INTRODUÇÃO: O presente estudo teve como objetivo verificar a coexistência de populações de Aedes aegypti e de Aedes albopictus em municípios do Estado do Paraná e Santa Catarina com diferentes formas de urbanização, onde ocorrem casos de dengue, e avaliar a susceptibilidade ao organofosforado temephos. MÉTODOS: O número de ovos por ovitrampa foram contados (sem distinguir a espécie) e colocados para eclosão e posterior identificação das espécies. A análise das populacões foi conduzida para determinar aleatoriedade e agregação usando a razão variância/média (índice de dispersão). A susceptibilidade ao temephos foi avaliada para determinar e estimar as razões de resistência RR50 e RR95. As ...